Il pacco-dono in ambito migratorio. Scambio di beni tra Cilento e fuori continente (dalla fine del secolo XIX) - Domenico Ienna (EtnoAntropologia, 2014)
Anthropological analysis of the gift wraps, which were sent towards and from Cilento (central-southern part of Salerno province) villages, in the field of emigration towards Americas and Australia,starting from the end of nineteenth century.